To find the x-intercepts of the polynomial function \( k(x) = 4x(1 − 2x)(3x + 4) \), we set the function equal to zero:
\[ 4x(1 - 2x)(3x + 4) = 0 \]
This equation will be zero if any of its factors is zero. We can find the x-intercepts by solving each factor individually:
-
From the first factor: \( 4x = 0 \)
- This gives: \( x = 0 \)
-
From the second factor: \( 1 - 2x = 0 \)
- Solving for \( x\): \[ 2x = 1 \implies x = \frac{1}{2} \]
-
From the third factor: \( 3x + 4 = 0 \)
- Solving for \( x\): \[ 3x = -4 \implies x = -\frac{4}{3} \]
So the x-intercepts of the function \( k(x) \) are:
- \( \left(0, 0\right) \)
- \( \left(-\frac{4}{3}, 0\right) \)
- \( \left(\frac{1}{2}, 0\right) \)
Therefore, the correct response is: \[ \left( -\frac{4}{3}, 0 \right), \left( 0, 0 \right), \left( \frac{1}{2}, 0 \right) \]